(untitled) (SCIÉNDO INGENIUM, 2021)
The purpose of the research was to determine the influence of the quality of outpatient medical care on the complaints and claims system at Albrecht 2020 hospital. This research was quantitative, cross-sectional and causal correlational. The sample consisted of 146 users of the external consultation; the instruments were valid and reliable. The information was processed with SPSS V26 software. The results were presented in frequency distribution tables. The survey technique was used with two Likert scale questionnaires. The information analysis was carried out using descriptive and inferential statistics, as tools for data processing, the statistical program SPSS, version 23, was used. It is concluded that there is a significant influence on the quality of medical care in the outpatient clinic. Albrecht hospital; finding a statistical contingency coefficient of Kendall’s Tau-b test = -, 059, with a level of significance less than 5% (P <0,05).